The Relationship Between Parenting Patterns and Toddler Development (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2021)
Toddler period is a period of basic growth that will influence and determine the next child's development. In addition, toddlerhood is a critical period, where useful stimulation is needed in order to develop so that it needs attention from the environment, especially parents so that if it does not support it will hinder the development of children. The role of parents in child development is one of the parenting styles applied to children, including democratic parenting, permissive parenting and authoritarian parenting. This study aims to determine The Relationship Between Parenting Patterns with The Toddler Development in Cikampek City of Karawang District in 2021. This study uses a correlational analytic study with a Cross Sectional design. The sample in this study were 69 mothers who had a toddler ages 12, 15, 18, 21, 24, 30, 36, 42, 48 months. The sampling technique used was purposive sampling technique. The research instrument consisted of a parenting patterns questionnaire and a developmental pre-screening questionnaire (KPSP). The data were analyzed using the chi square correlation test with a significant level <0.05 to determine the relationship between parenting patterns and the toddler. The results showed that relationship between parenting patterns and the toddler development had a p value 0, 000 (p <0.05).The conclusion of the research is there is a significant relationship between parenting patterns and the toddler development. Keywords: Parenting Pattern, Toddler Development